The role of microRNAs in erectile dysfunction: From pathogenesis to therapeutic potential - Song, Jingyu; Wang, Jiaxin; Liu, Kang; Xu, Wenchao; Sun, Taotao; Liu, Jihong (Frontiers in Endocrinology, 2022)
Erectile dysfunction (ED) is a common male sexual dysfunction disease, and it was predicted that the number of ED patients worldwide will reach 322 million by 2025. However, the pathogenesis of ED is complex and the current treatment options are still limited, so it is urgent to explore new treatment strategies. Recent studies have shown that microRNAs (miRNAs) play an important role in ED, and these single-stranded non-coding small RNA molecules are involved in key pathophysiological processes in the occurrence and development of ED. Therefore, miRNAs have remarkable potential as therapeutic targets in ED. Here, this review introduces the physiological basis of erectile function and the pathophysiological changes in ED and summarizes the current knowledge on the expression, biological functions, and molecular mechanisms of miRNAs in ED, especially the potential of miRNA-targeted therapies to improve ED. This review will provide a comprehensive view of the role of miRNAs in the pathogenesis of ED and the potential value of miRNAs in the treatment of ED.